A shear strength model for anisotropic blocky rock masses with persistent joints - Shen, Jiayi; Shu, Zheng; Cai, Ming; Du, Shigui (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2020)
The Mohr-Coulomb (MC) shear strength parameters, cohesion c and angle of friction φ, are required in numerical models. Currently, the geological strength index (GSI) system has been widely used for estimating shear strength of blocky rock masses in rock engineering. However, the GSI system does not include the effect of joint orientation β on the mechanical properties of a rock mass, which means that the shear strength model cannot reflect anisotropic rock mass strength behavior caused by joint orientation. In this research, UDEC-based synthetic rock mass models, which are calibrated by experimental data, are adopted to study the effect of joint orientation on the shear strength of blocky rock masses with two perpendicular joint sets. The values of cohesion c and angle of friction φ estimated from the numerical simulation are compared with those calculated from the empirical shear strength models based on the GSI system. Comparison of the results shows that the existing empirical model overestimates the shear strength of rock mass when 10° <β < 45°, which may impose a risk on engineering design. To rectify the problem, based on the analysis of shear strength parameters of rock masses with various joint orientations, anisotropic weighting factors are proposed to modify the existing model. The proposed modified model is capable of providing conservative but more accurate estimation of the shear strength of rock mass, which is important for safe engineering designs.